Dual beam Yagi patch antenna - Samree, S.; Getjulom, S.; Teangrod, S.; Kittiyanpunya, C.; Krairiksh, M. (My University, 2015)
This paper presents a dual beam Yagi patch antenna. The antenna operates in the ISM band of 2.41 and 2.45 GHz. It consists of rectangular patch fed at two different probe positions. The patch has two reflectors each provides directional pattern in two perpendicular directions. The isolation is better than 20 dB and directivity is more than 3 dBi. This antenna can be applied for receiving video signals from wireless cameras.